Regional integration and economic development - Saavedra Rivano, Neantro; Hosono, Akio.; Stallings, Barbara (New York : Palgrave, 2001)
The main objective of this book is to compare the ways in which regional integration has been evolving in the Americas and in East Asia, and examine the relation between regional integration initiatives and national development strategies.
Includes bibliographical references and index.
osa; 28/09/16
Loans
Keywords: International economic integration; Regional economics; Asia; Pacific Area; Southeast Asia; Latin America